Sosialisasi Penyusunan Program Latihan Fisik Bagi Atlet - Arya T Candra; Mislan; Moh. Agung Setiabudi; Edi Irwanto (Fakultas Teknik, Universitas PGRI Banyuwangi, 2021)
Physical condition is one of the most important elements that significantly affect the performance of an athlete. To improve the physical condition of an athlete, it takes an exercise program that is structured systematically and in accordance with the rules in the principles of training. The Sports Teacher Working Group or commonly known as KKGO is a collection of sports teachers who act as coaches and trainers for students who have talent in several sports. This service activity will be carried out on November 2-3, 2021 at the Untung Suropati Stadium Hall, Tembokrejo, Muncar District, with a duration of 3 hours/day. This service activity is in the form of socialization related to the preparation of physical exercise programs in accordance with the correct procedures and rules. The result of this community service program is that the coaches are able to develop a physical exercise program for athletes and in accordance with the rules contained in the principles of the training program.